Efek cahaya terhadap pertumbuhan dan mortalitas pada ikan kerapu cantang (Epinephelus fuscoguttatus lanceolatus) - Hama Pati, Maya; Lukas, Ade Yulita Hesti; Ratoe Oedjoe, Marcelien Dj (Nusa Cendana University, 2023)
This research aims to determine the effect of different lights on cannibalism in cantang grouper (Epinephelus fuscoguttatus lanceolatus) fry and to find out what types of colors can suppress cannibalism. The test fish used were 36 cantang grouper seeds of the same size, namely 6-8 cm. 3 fish were kept in each unit/research container. The experimental design used RAL with 4 treatments and 3 repetitions. The treatments consisted of treatment A (red light), treatment B (blue light), treatment C (green light) and treatment D (no light). The results of the research show that the influence of different light colors greatly influences fish mortality and growth and treatment B with blue in this study can suppress cannibalism and growth of cantang grouper. Absolute length growth was 1.1 cm in treatment B, and absolute weight growth was 2.2 g in treatment B (blue).